CHEMICAL INTERACTIONS ON COUNTER ELECTRODE SURFACE OF NANOSTRUCTURED POLYIANILINE IN DYE-SENSITIZED SOLAR CELLS (DSSC) - Reza, Muhammad
With the accelerating development of platinum-free Dye-Sensitized Solar Cells (Pt- Free DSSC), many researchers have studied ways to integrate carbonaceous materials as an efficient counter electrode (CE) in Pt-Free DSSC. Among conductive polymers, polyaniline (PANI) has received remarkable attention because it has controllable electrical conductivity, easy synthesis method, good environmental stability, and interesting redox properties associated with the chain heteroatoms. The problem occurs during the electrochemical reaction between PANI Emeraldine Salt (PANI ES) and triiodide (I3-) ion. The redox reaction between PANI ES and I3- ion leads to a negative standard potential cell at the CE surfaces. However, the potential cell value (Ecell) under nonstandard conditions follows the Nernst equation to facilitate the reaction. Therefore, a positive Ecell can still be obtained by increasing the adsorbed I3- ions on the PANI surface. Increasing the PANI surface area at the CE/electrolyte interface is another approach that can be carried out besides increasing the I3- ion concentration in the electrolyte solution. However, PANI ES is synthesized using a rapid mixing method that produces irregularly shaped particles with smooth surface morphology and low surface area. Meanwhile, the adsorption process is crucial in determining the sustainability of I3- reduction and charge circulation in DSSC.